Agenda do meio ambiente no Jornal Nacional : avaliação da qualidade da relevância temática - Brandi, Daniel Pereira (2018)
The research is an experimental quality evaluation of the Jornal Nacional (JN) coverage on the environmental theme, based on the relevance requirement (Feitoza, 2016). The verification took place in three movements: assembly of the map of environmental thematic units; the Content Analysis (Bardin, 1977), which recorded the macro and micro themes present in the coverage; and the construction of relevance matrices, according to the methodology proposed by the Journalistic Agenda Guide (Guerra, 2016). The main objective is to demonstrate that the adoption of quality parameters extends the fulfillment of the expectations demanded by the priority group: the audience. We define a reference model applicable to newsrooms, based on three spheres of the environmental agenda (McCombs, 2009): media, represented by the empirical survey of 12 months of exibition on JN; public, based on consultation with environmental experts; and political, from documents of the Ministry of Environment of Brazilian federal government and the United Nations (UN). The Applied Research immerses in the content offered by the journalistic product, in order to reveal traces of thematic priority and of nonobservance to ethical aspects of accountability, that is, insufficient attention to emblems of the modern democratic essence, such as the right to information, transparency and accountability. At the end of the analysis, it is possible to identify the degree of correspondence between the Reference Relevance Factor, defined by the public and political agendas and the Factor of Relevance Determined in coverage of JN. We mainly offer a set of indicators to measure the news, which can contribute to the qualification of the processes of planning, production, monitoring and dissemination of results.